2012
DOI: 10.1021/jf301281a
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation of Baked Chicken Wrapped with Antimicrobial Apple and Tomato Edible Films Formulated with Cinnamaldehyde and Carvacrol

Abstract: The addition of plant essential oils to edible films and coatings has been shown to protect against bacterial pathogens and spoilage while also enhancing sensory properties of foods. This study evaluated the effect of adding 0.5 and 0.75% carvacrol (active ingredient of oregano oil) to apple- and tomato-based film-forming solutions and 0.5 and 0.75% cinnamaldehyde (active ingredient of cinnamon oil) to apple-based film-forming solutions on sensory properties of cooked chicken wrapped with these films. Paired p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 33 publications
1
36
0
4
Order By: Relevance
“…Overall, the results suggest that preference of chicken meat rinsed with the extract may be positively or negatively influenced by incorporation of flavourful components such as black pepper. A similar observation was reported by Du et al (2012); Carvacrol at 0.5% incorporated in edible apple film reduced the preference of wrapped cooked chicken meat, while the same concentration of carvacrol in edible tomato film showed no effect on preference of wrapped cooked chicken meat. Comments from untrained panelists indicated that the extract had a slightly bitter taste on chicken piece surface.…”
Section: Sensory Evaluationsupporting
confidence: 87%
“…Overall, the results suggest that preference of chicken meat rinsed with the extract may be positively or negatively influenced by incorporation of flavourful components such as black pepper. A similar observation was reported by Du et al (2012); Carvacrol at 0.5% incorporated in edible apple film reduced the preference of wrapped cooked chicken meat, while the same concentration of carvacrol in edible tomato film showed no effect on preference of wrapped cooked chicken meat. Comments from untrained panelists indicated that the extract had a slightly bitter taste on chicken piece surface.…”
Section: Sensory Evaluationsupporting
confidence: 87%
“…It may also be noted in the same figure that starch films are transparent and perhaps, such transparency downgrades the colour attributes of tastemaker powder whilst keeping tea unaffected. Thus, as mentioned earlier for protein and fruit based packaging films (McHugh & Senesi, 2000;Jang et al, 2011;Du et al, 2012) starch based films also have the ability to preserve sensorial attributes of food materials.…”
Section: Quality Attribute Ranking Of Individual Tea and Tastemaker Smentioning
confidence: 85%
“…Apple wraps applied on fresh-cut apple slices were more effective than coatings to increase shelf life, reduce moisture loss and browning (McHugh & Senesi, 2000). According to Du et al (2012), paired sensory preference tests indicated no difference between baked chicken wrapped with tomato and apple films containing 0.5% plant antimicrobials, such as carvacrol and cinnamaldehyde, compared to chicken wrapped with tomato or apple films without antimicrobials added. Reports on the retention/loss of sensory attributes of foods packed in starch based films is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpenes are mostly used in industry to mask odors (Osada et al, 2013), scents for all purposes, food additive (Yu et al, 2012), flavor adjuvant (Fukumoto et al, 2006;Heck, 2010), pharmaceutical adjuvants (Narishetty and Panchagnula, 2004) and as active ingredients in some ointments or topical creams used to relieve symptoms of chest congestion, cough and asthma (Abanses et al, 2009;Ando et al, 1993). Despite these applications, the monoterpenes have several biological activities but the microbial activity is highlighted for many of them, such as thymol (Perez-Alfonso et al, 2012), eugenol (Pei et al, 2009;Sleha et al, 2012;Veras et al, 2012), cinnamaldehyde (Du et al, 2012), alpha-pinene (Sartorelli et al, 2007), limonene (Di Pasqua et al, 2006), trans-cinnamaldehyde, perillaldehyde, citral, eugenol, citronellal (Sato et al, 2006;Sleha et al, 2012), pcymene (Kisko and Roller, 2005;Rattanachaikunsopon and Phumkhachorn, 2010) and carvacrol (Didry et al, 1993).…”
Section: Discussionmentioning
confidence: 99%